Śrīmat Kurupara Cuvāmikaḷ tiruvāymalarntaruḷiya Citamparac ceyyuṭkōvai - Kumarakurupara Aṭikaḷ, 17th cent (SAMP early 20th-century Indian books project ;, 1937)
Hymns in praise of holy places in Chidambaram, India.